2019
DOI: 10.1177/1073110519897729
|View full text |Cite
|
Sign up to set email alerts
|

Where Stool is a Drug: International Approaches to Regulating the use of Fecal Microbiota for Transplantation

Abstract: Regulatory agencies vary widely in their classification of FMT, with significant impact on patient access. This article conducts a global survey of national regulations and collates existing FMT classification statuses, ultimately suggesting that the human cell and tissue product designation best fits FMT's characteristics and that definitional objectives to that classification may be overcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 58 publications
(61 reference statements)
0
25
0
Order By: Relevance
“…In 2018, the stool bank’s protocol was designed principally to improve the safety and accessibility of FMT for treating C. difficile infection in a specific regulatory environment, 37 using donors from a limited geographic location, and guided by the scientific and medical understanding of FMT at the time. The protocol described here would require modification if implemented in a different regulatory environment 23,32 or geography 47 . Furthermore, as the field’s understanding of the safety profile and molecular mechanisms of FMT improves, there will be further opportunities to optimize human-derived microbial therapies in general and stool banking protocols in particular.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, the stool bank’s protocol was designed principally to improve the safety and accessibility of FMT for treating C. difficile infection in a specific regulatory environment, 37 using donors from a limited geographic location, and guided by the scientific and medical understanding of FMT at the time. The protocol described here would require modification if implemented in a different regulatory environment 23,32 or geography 47 . Furthermore, as the field’s understanding of the safety profile and molecular mechanisms of FMT improves, there will be further opportunities to optimize human-derived microbial therapies in general and stool banking protocols in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are differences between stool banks, in part due to variation in FMT regulation between countries, 32 stool banks generally adhere to a common-six part methodology, shown below. 5,21,[23][24][25]31,33,34 In some banks, these six elements are joined together by rigorous quality systems.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the FDA's enforcement discretion policy has allowed the practice of FMT without mandated systematic collection of safety data in the vast majority of patients. Therefore, this opinion is based on limited observational case series, several carefully conducted open-label trials, a few randomized controlled trials, 32 as well as collective experiences of many individual physicians using FMTs in their clinical practices.…”
Section: Development Of Microbiota-based Therapeuticsmentioning
confidence: 99%
“…Arguments for using FMT as a treatment for rCDI were initially based on observational studies, such as case series, and data from small, unblinded trials. 43 These studies were not designed to produce evidence of efficacy for FDA approval of stool as a treatment for rCDI and were not regulated by the FDA. Results from these initial studies indicated that FMT led to resolution of rCDI symptoms in 89% to 94% of patients.…”
Section: Microbiota Transplants Lack High-quality Evidencementioning
confidence: 99%